Adulthood as a universal educational goal - Walt, J. L. van der (Koers, 1979)
In some educational circles the aim of pedagogy (the leading/guiding of children) is circumscribed or indicated as “adulthood”, “which is commonly accepted as the first and the natural destination of the child who is on his journey through the world. Education ...is to lead/guide or to accompany a child on his way to the adulthood worthy of a human being as its aim” (Gunter, 1970, p. 9). In this respect one comes across several (vague) references in literature to “ the idea of adulthood” , the “norm figure of adulthood” being “ the natural destination of every child”, “the figure (form) of adulthood” (Landman & Gous, 1969, p. 80), “the ideal figure of adulthood” (as opposed to a “phantom of adulthood”), “a norm figure which is worth striving for” (ibid, p. 81). The authors just referred to rightly come to the conclusion that “content should be given to the idea of adulthood” (Landman, Roos & Liebenberg, 1971, p. 145).